Forum, Round Table and Vinegar: Managing the Cellulose Acetate Microfilm Challenge - Field, Clive (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2005)
This final paper from CAMF 2005 is intended to provide some kind of synthesis and commentary on the Forum, plus an update on the third International Round Table on Preservation Microfilm (hereafter referred to simply as the Round Table) which took place, and which I chaired, the day before. In offering these concluding reflections on the Forum, I hope to give a sense of the ways in which the agenda for tackling the cellulose acetate microfilm challenge around the world can be, and is being, taken forward.